Willingness to Pay for Mandibular Overdentures: A Societal Perspective. (January 2020) - Srivastava, A.; Esfandiari, S.; Madathil, S.A.; Birch, S.; Feine, J.S.
Objectives: Dental services in many countries are funded out-of-pocket by patients whose acceptance of a dental treatment depends on their valuation of it. Using a willingness-to-pay (WTP) strategy, this study aimed to determine how people who do not wear dentures value the benefits of dentures retained by implants and what factors explain variations in WTP among subjects. Methods: Telephone numbers of a representative Canadian sample were obtained from a consumer database provider. Respondents completed either an internet-based or telephone survey with 3 payment scenarios: paying oneself (out-of-pocket), coverage with private health insurance, and publicly financed through additional taxes. Personal information data (e.g., age, income) were used as independent variables in regression models to assess the determinants of WTP amounts. Results: Among 1, 096 respondents, 317 participated in the survey (response rate, 28.9%). The mean WTP of participants (mean ± SD age: 41.2 ± 0.6 y; 54.3% male) who were dentate/partially edentate was $5, 347 for implant overdentures. Considering a 1 in 5 chance of becoming edentate, they were willing to pay $26.93 as monthly payments for private insurance. They were also willing to pay an additional yearly tax of $103.63 to support a public program. WTP private payments increased substantially with increase in household income and dental needs. Conclusion: This preference study provides information to dentists, insurance companies, and policy makers on what dentate people are willing to pay for implant overdentures, whether directly or with insurance/government coverage. Knowledge Transfer Statement: This study provides results of interest to many stakeholders. For clinicians, the results reveal what people are willing to pay for implant overdentures for themselves. It also provides information to employers and insurance companies on how people value having coverage for this kind of service. Furthermore, it provides public policy makers the value that people place on public funding of such treatments and how they would support a decision to publicly fund such a treatment.